Prospects of Development of Agricultural Branches of the Regions of the Russian Federation: Correlation Models and Effectiveness of Management - A. Urasova, Anna; N. Pytkin, Aleksander; Yu. Zagoruyko, Igor; V. Plotnikov, Andrei; P. Cherdantsev, Vadim (International Journal of Engineering and Technology, 2018)
Currently, Russia faces an urgent need for accelerated development of agricultural branches and rural infrastructure. The solution of the tasks of agricultural management is one of the most urgent problems of determining the reserves of growth of agricultural production in each of the Russian regions. In this regard, the authors set a goal to develop and evaluate correlation models describing the dependence of the volume of production of agricultural branches in the regions of the Russian Federation on the number of investments and the commissioning of fixed assets. The authors justify the choice of independent factors. The study was based on the economic and mathematical modeling of empirical spatial data, calculated on the basis of official statistical information on the regions of the Russian Federation. The conducted research permitted to identify factors, which directly determined the volumes of production in agriculture, to propose the use of high-quality correlation models to describe this effect, to prove that the economies of the examined regions did not reach saturation with agricultural products and there were significant reserves for their further development. The developed correlation models are effective tools for analyzing the development of the industry, and can also be used as management tools that allow for the assessment of the effectiveness of the use of the made investments, as well as the commissioning of fixed assets in the agriculture of each of the examined regions. The results of the research are of scientific and practical importance. They can be used in research and monitoring of agricultural development in the regions, determining the resource requirements, which are necessary for the development of agricultural industries, as well as the development of sectoral and integrated projects and agricultural development programs.